2020
DOI: 10.11002/kjfp.2020.27.7.880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chlorogenic acid and rutin contents and antioxidant activity of Dendropanax morbiferus extracts according to ethanol concentration

Abstract: This study investigated the phenolics (TP) and phytochemical contents and radical-scavenging activity of ethanol extracts of Dendropanax morbiferus parts (leaf, stem, and root). The contents of chlorogenic acid (CA) and rutin (RT) and radical-scavenging activity of all extracts by parts were in the order of leaf, stem and root. In the case of leaf, the TP contents were 2.15-2.52 mg/g when extracted with hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine as high as those of Hwang et al [41] (Table 1). is showed that the difference in CGA content and rutin depends on the harvesting location, season, and extraction conditions of DML [42].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Evidence-Based Complementary and Alternative Medicine as high as those of Hwang et al [41] (Table 1). is showed that the difference in CGA content and rutin depends on the harvesting location, season, and extraction conditions of DML [42].…”
Section: Discussionmentioning
confidence: 81%
“…Rutin is an essential flavonoid in herbal foods, which significantly reduced SUA levels in mice with hyperuricemia [39] and increased urinary UA concentration in rats with renal dysfunction [40]. In a previous study [41], the CGA and rutin contents from DML extracts in 70% ethanol for 2 h were the highest at 12.33 and 14.09 mg/g, respectively. In another study, the CGA concentration in the 30% DML ethanol extract collected in November was the highest at 36.55 mg/g, and the rutin content in the 60% DML ethanol extract collected in May was the highest at 116.71 mg/g [42].…”
Section: Discussionmentioning
confidence: 90%
“…Extracts were prepared from DMLs as previously described [ 12 ]. Briefly, after washing and drying fresh DMLs, these were extracted using hot-water.…”
Section: Methodsmentioning
confidence: 99%
“…Total polyphenol content was quantitated, following a previously published protocol [ 12 ]. Briefly, 1 mL of the DML extracts was diluted with 9 mL water and oxidized with 1 mL of diluted Folin-Ciocalteu reagent (Sigma-Aldrich) for 8 min at room temperature followed by neutralization with 4 mL sodium carbonate solution (7.5%, w / v ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation